Addition of magnetic resonance imaging to real time trans-rectal ultrasound-based treatment planning for prostate implants - Petronek, Michael (J Contemp Brachytherapy, 2019)
PURPOSE: The greater soft tissue contrast of magnetic resonance imaging (MRI) allows improved accuracy in prostate contouring compared to transrectal ultrasound (TRUS) and helps in identifying specific regions within the prostate. This study attempts to evaluate the potential benefit of MRI-TRUS fusion in treatment planning for more accurate prostate contouring and tumor dose escalation. MATERIAL AND METHODS: 14 patients with previous MRI-guided prostate biopsy and an low-dose-rate (LDR) permanent prostate seed implant have been selected. The prostate and tumor (5 patients) were contoured on the MRI images by a radiologist. The prostate was also contoured on TRUS images during LDR procedure together by a urologist and radiation oncologist. MRI and TRUS images were rigidly fused to compare prostate contours in MRI and TRUS. Prostate was then re-contoured by the radiation oncologist using this fusion. Moreover, V(100), V(150), and D(90) differences were evaluated for localized tumor compared to prostate with negative values indicating cold tumor regions. These cases were re-planned to simulate dose escalation. RESULTS: The prostate volume was contoured 8 ±10% smaller in TRUS images, compared to MRI images. The mean percent difference in tumor (compared to prostate) V(100) was 0.3 ±–0.4%, V(150) was –0.7 ±–24.8%, and D(90) was 0.2 ±–12.1%. For the posteriorly located tumors (2 cases), V(100) was 0.0 ±–0.3%, D(90) was 9.5 ±–3.0%, and V(150) was 26.1 ±–5.4%. For anteriorly located tumors (3 cases), V(100) was 0.4 ±–0.4%, D(90) was –6.0 ±–11.9%, and V(150) was –18.5 ±–14.4% (became 15.6 ±14.6% after re-plan). CONCLUSIONS: The MRI-TRUS image fusion is a feasible tool for the visualization of the prostate gland, particularly at the apex and base of the gland. Tumor identification presents the potential for dose escalation using fusion, especially for anteriorly located tumors.